2021
DOI: 10.2217/fon-2021-0964
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Ibrutinib dose Reductions, Holds and Discontinuations in Chronic Lymphocytic Leukemia

Abstract: Aim: A retrospective chart review of ibrutinib-treated patients with chronic lymphocytic leukemia (CLL) was conducted. Patients & methods: Adults with CLL who initiated ibrutinib were followed for ≥6 months (n = 180). Results: Twenty-five percent of first-line ibrutinib patients experienced ≥1 dose reduction, mainly due to adverse events (AEs; 79%). Treatment discontinuations and dose holds occurred in 20 and 34% of patients, respectively, most commonly due to AEs (73 and 74%). Approximately one-quarter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“… 20 , 23 In a real-world study investigating dose reductions or discontinuations in patients with CLL, 22.8% of patients experienced a dose reduction and 20.6% discontinued ibrutinib due to an adverse event (AE). 30 In this study, the most common AEs leading to discontinuation of ibrutinib were atrial fibrillation (24% of patients who discontinued ibrutinib), gastrointestinal disorders (24%), infections/infestations (19%), hematologic abnormalities (16%), and fatigue (14%). In another real-world study of ibrutinib in patients with CLL, 91/209 (43.5%) patients had a temporary dose interruption, and after a median of 20 months on therapy, 37/209 (17.7%) patients discontinued therapy due to a toxicity, including infection (21.6%), cardiovascular event (13.5%), hematologic toxicity (13.5%), bleeding (10.8%), atrial fibrillation (8.1%), diarrhea (8.1%), musculoskeletal pain (5.4%), or other (18.9%).…”
Section: Introductionmentioning
confidence: 70%
“… 20 , 23 In a real-world study investigating dose reductions or discontinuations in patients with CLL, 22.8% of patients experienced a dose reduction and 20.6% discontinued ibrutinib due to an adverse event (AE). 30 In this study, the most common AEs leading to discontinuation of ibrutinib were atrial fibrillation (24% of patients who discontinued ibrutinib), gastrointestinal disorders (24%), infections/infestations (19%), hematologic abnormalities (16%), and fatigue (14%). In another real-world study of ibrutinib in patients with CLL, 91/209 (43.5%) patients had a temporary dose interruption, and after a median of 20 months on therapy, 37/209 (17.7%) patients discontinued therapy due to a toxicity, including infection (21.6%), cardiovascular event (13.5%), hematologic toxicity (13.5%), bleeding (10.8%), atrial fibrillation (8.1%), diarrhea (8.1%), musculoskeletal pain (5.4%), or other (18.9%).…”
Section: Introductionmentioning
confidence: 70%
“…A large multicenter retrospective study of 231 patients treated in the relapsed setting showed a discontinuation rate of 20.9% due to toxicity, with atrial fibrillation, infection, pneumonitis, bleeding, and diarrhea being the most common toxicities leading to discontinuation 5 . Another US based study and data from the Swedish CLL group also showed a discontinuation rate of around 20% due to toxicity 6,7 …”
Section: Inhibitors Of Btk In Relapsed/refractory Cllmentioning
confidence: 99%
“… 5 Another US based study and data from the Swedish CLL group also showed a discontinuation rate of around 20% due to toxicity. 6 , 7 …”
Section: Inhibitors Of Btk In Relapsed/refractory ...mentioning
confidence: 99%
“…2 Retrospective analyses have shown that dose reductions of ibrutinib to 140-280 mg day −1 within 3 months from treatment initiation, due to adverse events or other causes, can minimize the adverse events without having inferior outcomes on long-term therapy. [3][4][5][6] CLL is a form of leukemia, with diverse biological and clinical characteristics. 7 The disease is characterized by abnormal B-lymphocyte accumulation in lymphoid tissues and blood.…”
Section: Introductionmentioning
confidence: 99%